2008
DOI: 10.1016/j.cell.2008.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Activation Controls Nuclear Localization of β-catenin during Canonical Wnt Signaling

Abstract: Canonical Wnt signaling critically regulates cell fate and proliferation in development and disease. Nuclear localization of beta-catenin is indispensable for canonical Wnt signaling; however, the mechanisms governing beta-catenin nuclear localization are not well understood. Here we demonstrate that nuclear accumulation of beta-catenin in response to Wnt requires Rac1 activation. The role of Rac1 depends on phosphorylation of beta-catenin at Ser191 and Ser605, which is mediated by JNK2 kinase. Mutations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
425
8
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 443 publications
(468 citation statements)
references
References 63 publications
31
425
8
4
Order By: Relevance
“…Similar observations could be achieved when the Ishikawa cells were transfected with a dominant negative Rac1 (N17Rac1) 26 (Figure 5f). Because Rac1 is a known target of Wnt5a signaling 35,36 that has been shown to be essential for cell polarity induction and epithelial function in various organs including the uterus, 9,11,37 we also analyzed the consequence of Rac1 deficiency on uterine Wnt5a expression.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Similar observations could be achieved when the Ishikawa cells were transfected with a dominant negative Rac1 (N17Rac1) 26 (Figure 5f). Because Rac1 is a known target of Wnt5a signaling 35,36 that has been shown to be essential for cell polarity induction and epithelial function in various organs including the uterus, 9,11,37 we also analyzed the consequence of Rac1 deficiency on uterine Wnt5a expression.…”
Section: Resultssupporting
confidence: 81%
“…Because the systemic Rac1 null mice are embryonic lethal owing to gastrulation defects, 24 to analyze the pathophysiological significance of Rac1 in early pregnancy events, we next used a progesterone receptor (Pgr)-driven Cre (Pgr cre/+ ) mouse model crossed with Rac1 floxed (Rac1 f/f ) mice to achieve uterine-selective deletion of Rac1. [25][26][27] As shown in To ascertain the stage-specific causes accounting for this obvious infertility, we subsequently analyzed the implantation status in mice missing uterine Rac1. Although all Rac1 f/f mice tested showed normal embryo implantation on day 5 morning (Figure 2j).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that total b-catenin level was clearly reduced (Figures 5a and b). In comparison with the PAK1-knockdown cells, nuclear b-catenin staining was further reduced in Rac1-knockdown cells (compare Figures 5a and 2c) and this is consistent with the previous report that Rac1/JNK2 controls b-catenin nuclear localization (Wu et al, 2008;Phelps et al, 2009). In addition, NSC23766, a Rac1 inhibitor, was also able to reduce total b-catenin in SW480 cells (Figures 5c and d).…”
Section: Rac1 Controls B-catenin Level and Phosphorylation Through Pak1supporting
confidence: 92%
“…However, it was argued recently that APC mutation alone probably is not sufficient to promote full b-catenin signaling (Anderson et al, 2002;Phelps et al, 2009). Mutation of K-Ras was often observed in more advanced colon cancer samples and it was suggested that a K-Ras/Rac1/ JNK2 cascade may further enhance b-catenin nuclear accumulation by JNK2-mediated phosphorylation of b-catenin at Ser191 and Ser605 (Wu et al, 2008;Phelps et al, 2009). However, Rac1 was also found being able to elevate cytosolic, as well as nuclear levels of b-catenin (Esufali and Bapat, 2004).…”
Section: Introductionmentioning
confidence: 99%